A Review of Financial and Management Accounting as the Basis of Financial Management - Hanafie, Saliha G; Bandera, Abdani D.; Usman-Macadaag, Omaimah M. (Indonesian Journal Publisher, 2025)
This study examines how financial and management accounting systems support effective financial management, with particular focus on transparency, governance, and strategic decision-making across corporate, SME, and public-sector contexts. Utilizing a qualitative literature review approach, the paper synthesizes peer-reviewed research, institutional reports, and academic books published between 2015 and 2025. Thematical analysis centers around three core dimensions: transparency and corporate governance in financial reporting, management accounting as a decision-support tool, and integration of accounting systems through digitalization and sustainability practices. The review finds that high-quality financial reporting reduces information asymmetry, strengthens governance, and enhances stakeholders’ confidence, while management accounting transforms financial and non-financial data into actionable insights that improve operational efficiency, cost control, and strategic planning. Integration of these systems, facilitated by digital technologies such as artificial intelligence, business intelligence, blockchain, and cloud accounting, further enhances real-time decision-making, predictive analytics, and organizational resilience. The effectiveness of these systems is contingent on financial literacy, technological readiness, and institutional capacity, with SMEs and public-sector organizations exhibiting unique challenges and opportunities. The study concludes that accounting systems serve not only as compliance mechanisms but also as strategic tools that link reporting, decision-making, and sustainability considerations.